Capital Structure and The Profitability of Listed Retail Firms - Kasozi, Jason Stephen (Journal of Economics and Behavioral Studies, 2018)
The South African retail sector continues to experience a decline in sales and returns amidst growing external competition and a drop in consumer confidence stemming from the recent credit downgrades in the country. Yet, firms in this sector appear to maintain high debt to equity levels. This study investigated whether the capital structure practices of these firms influence their profitability. A Panel data methodology, using three regression estimators, is applied to a balanced sample of 16 retail firms listed on the Johannesburg Securities Exchange (JSE) during the period 2008-2016. The analysis estimates functions relating capital structure composition with the return on assets (ROA). Results reveal a statistically significant but negative relationship between all measures of debt (short-term, long-term, total debt) with profitability, suggesting a possible inclination towards the pecking order theory of financing behaviour, for listed retail firms. Additionally, retail firms are highly leveraged yet over 75% of this debt is short-term in nature. Policy interventions need to investigate the current restrictions on long-term debt financing which offers longerterm and affordable financing, to boost returns. While this study’s methodology differs slightly from earlier studies, it incorporates vital aspects from these studies, and simultaneously specifies a possible model fit. This helps to capture unique but salient characteristics like the transitional effects of debt financing on firm profitability. It therefore delivers some unique findings on the financing behaviour of retail firms that both in form policy change, while stimulating further research on the phenomenon.